2011
DOI: 10.1177/003335491112600309
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hospitalizations with Antibiotic-Resistant Infections: U.S., 1997–2006

Abstract: Antibiotic-resistant infections are becoming increasingly commonplace in hospitalizations in the U.S., with a steady upward trend between 1997 and 2006. Antibiotic-resistant infections are increasingly being seen in younger patients and those without health insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 14 publications
0
39
1
1
Order By: Relevance
“…Analysis of the prevalence of antibiotic use showed that metronidazole was the most prevalent antibiotic, prescribed for 35.6% of We have witnessed a decline in the numbers of new antibiotics being marketed in recent years and the medical community is struggling to preserve our current armamentarium (12). Investigators and health-care officials in the United States and Europe are working on a more uniform approach to antibiotic stewardship.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the prevalence of antibiotic use showed that metronidazole was the most prevalent antibiotic, prescribed for 35.6% of We have witnessed a decline in the numbers of new antibiotics being marketed in recent years and the medical community is struggling to preserve our current armamentarium (12). Investigators and health-care officials in the United States and Europe are working on a more uniform approach to antibiotic stewardship.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial 16S rDNA Note: 1 The base "i" designates inosine; "K" denotes G/T; "R" indicates A/G; "Y" indicates C/T.…”
Section: Quantitative Pcr Primers/probes and Plasmidsmentioning
confidence: 99%
“…In the United States, the number of ARB-related hospitalizations continues to increase [1] with an estimated cost of up to $30 billion annually [2]. In recent years the importance of ARB has come to the forefront of many scientific disciplines including environmental microbiology.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is not only the high prevalence of resistance among bacteria that poses a threat, but also the rapid increase in levels of resistance. Mainous et al (2011) analysed the tendencies of antibiotic resistance in US hospitals during a 10-year period between 1997 and 2006. The results of the study showed a twofold increase in the number of infectionrelated hospitalizations with antibiotic resistance.…”
Section: Methicillin-resistant S Aureusmentioning
confidence: 99%